2012
DOI: 10.1111/j.1365-2702.2012.04103.x
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of hand hygiene compliance in paediatric wards

Abstract: Visitors had the lowest level of compliance yet owing to the nature of the clinical environments, nearly a quarter of care is delivered by them rather than healthcare workers, and so, this offers opportunities for specific future interventions aimed at families and carers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 33 publications
5
21
2
2
Order By: Relevance
“…The student nurses’ moment‐specific hand hygiene compliance was different across the five moments, with the highest compliance rate after touching patients or patient surroundings, and after body fluid exposure risk, and lowest before clean/ aseptic procedures, and touching patients or patient surroundings. These results correspond with findings in observational studies of healthcare workers (Allegranzi & Pittet, ; Alsubaie et al., ; Randle et al., ; Scheithauer & Lemmen, ). That only 77% of the students cleaned their hands before touching patients or patient surroundings, is a concern, due to the risk of cross‐contamination between patients.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The student nurses’ moment‐specific hand hygiene compliance was different across the five moments, with the highest compliance rate after touching patients or patient surroundings, and after body fluid exposure risk, and lowest before clean/ aseptic procedures, and touching patients or patient surroundings. These results correspond with findings in observational studies of healthcare workers (Allegranzi & Pittet, ; Alsubaie et al., ; Randle et al., ; Scheithauer & Lemmen, ). That only 77% of the students cleaned their hands before touching patients or patient surroundings, is a concern, due to the risk of cross‐contamination between patients.…”
Section: Discussionsupporting
confidence: 90%
“…Although student nurses in our study achieved relatively high compliance scores, some of them neglected hand hygiene in high‐risk situations, failing to protect patients and themselves against HAIs. While hand hygiene performance is regarded as a basic procedure, the hand hygiene context is not, as numerous factors influence compliance in busy, complex and dynamic work circumstances (Carter et al., ; Erasmus et al., ; Randle et al., ). Chassin () identified 41 different causes of noncompliance in eight hospitals in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is satisfying to note that disinfection received priority, as this is one of the most important procedures in preventing the spread of infections in healthcare settings (Boyce & Pittet, ). Few studies regarding hand hygiene have been performed in pediatric settings; however, recent observational studies showed that RNs’ adherence to hand‐hygiene protocol in pediatric units was 75% (Randle, Firth, & Vaughan, ) and 65%–88% in neonatal units (Helder, Brug, Looman, van Goudoever, & Kornelisse, ), figures that align with our results.…”
Section: Discussionsupporting
confidence: 89%